Current approach to diagnosis of inflammatory myopathies: Clinical features and myositis antibody profiles - Vineeta Shobha; Liza Rajasekhar (Wolters Kluwer Medknow Publications, 2022)
Diagnosis of inflammatory myositis has been made easier with the availability of commercial assays for myositis-specific and myositis-associated antibodies. Clinico-serological association studies have permitted a better definition of clinical subsets. Myositis-specific auto-antibodies are highly specific and non-overlapping, whereas myositis-associated antibodies are those seen also in other connective tissue disorders such as systemic lupus erythematosus, primary Sjogren's syndrome, and idiopathic pulmonary auto-immune fibrosis. Their value is pronounced when clinical features are subtle or non-specific or when the muscle is not the primary organ involved. Overall, the muscle-specific and myositis-associated antibodies have changed the landscape in terms of diagnostic utility, prognostication, and the approach to organ-specific evaluation and management of idiopathic inflammatory myopathies (IIMs).